How the gene-editing in medicine and public health practice could stand the test of bioethics - Zang, Zheng; Chen, Yueqin (Acta Bioethica, 2021)
In recent years, gene editing is increasingly used as one of the technical means to solve public health problems. The great progress made in the field of life science and gene-editing technology has made it possible for humans to control and alter human physiological characteristics through gene-editing technology and created a broad application prospect for this technology. However, gene-editing technology has faced with many significant ethical risks, and human gene editing experiments have been banned for a long time in the past. Realistic technological breakthroughs and the emergence of real cases force the ethics circle to re-examine this issue. Through the analysis and trade-off of the potential benefits and ethical risks of human gene-editing technology, it can be found that different applications of human gene editing for different purposes are considered to have different acceptability. Among them, human gene editing for medical purposes has no fundamental moral barriers, human gene editing for purposes of enhancement cannot be allowed by ethics and reality in the current social environment, and human gene editing for purposes of transformation fundamentally violates ethical norms. Therefore, gene editing can be allowed if it is only used to solve human medical and public health problems.